Decline in submerged macrophyte beds in the Pearl River Delta, China, 2015–2020 - Yanyi Zeng; Wanling Yang; Haiyan Li; Zini Lai; Chao Wang; Qianfu Liu; Yuan Gao; Yongzhan Mai (Ecological Indicators, 2022)
To maintain submerged macrophyte beds (SMBs), a sound understanding of the factors that influence their succession is required. The aim of this study was to determine what influenced the succession of SMBs in a tidal river system, namely the Pearl River Delta, China (PRD). Surveys were carried out from 2015 to 2020 and a range of environmental (16) and ecological parameters were measured that could support an examination of the distribution and variation in SMBs. The coverage area, species richness, and biomass were measured at the community level, while nine morphological traits of the dominant species, Vallisneria denseserrulata, were measured at the population level. The results showed that, in 2015, the SMB community was distributed in sporadic patches and the community was dominated by multiple species. In 2018, V. denseserrulata grew continuously from February to August in all sections but its growth through the overwintering period (December) followed two patterns: recession (Pattern 1) or continuous growth (Pattern 2). Principal component analysis highlighted that the clonal growth ability, sexual propagation allocation, and perennial growth were related to different patterns of V. denseserrulata growth in the overwintering period. Pattern 1 was characterized by a low clonal growth ability and no sexual propagation, while Pattern 2 was characterized by a strong clonal growth ability and sexual propagation over winter. In 2019, the community was dominated by a single species of V. denseserrulata and macrophytes had disappeared from most river sections. The results from redundancy analysis implied that the decline in the SMBs from 2015 to 2020 was probably related to increases in the (1) TP concentrations in the sediment, (2) occupation of SMB habitats, and (3) annual river runoff in pre-flooding periods.